2004
DOI: 10.1103/physrevd.70.106005
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the veil: Inner horizon instability and holography

Abstract: We show that scalar perturbations of the eternal, rotating BTZ black hole should lead to an instability of the inner (Cauchy) horizon, preserving strong cosmic censorship. Because of backscattering from the geometry, plane wave modes have a divergent stress tensor at the event horizon, but suitable wavepackets avoid this difficulty, and are dominated at late times by quasinormal behavior. The wavepackets have cuts in the complexified coordinate plane that are controlled by requirements of continuity, single-va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 43 publications
4
95
1
Order By: Relevance
“…Special care is needed when ν is an integer. 13 This makes the large ν limit more subtle. Even at the leading order, one has to take into account of an infinite number of classical paths in the WKB approximation [37].…”
Section: Jhep04(2006)044mentioning
confidence: 99%
See 1 more Smart Citation
“…Special care is needed when ν is an integer. 13 This makes the large ν limit more subtle. Even at the leading order, one has to take into account of an infinite number of classical paths in the WKB approximation [37].…”
Section: Jhep04(2006)044mentioning
confidence: 99%
“…Going to momentum space (2.10) becomes (see the appendix for a definition of the Fourier transform) 13) where l denotes the angular momentum on S 3 . The Feynmann (retarded) propagator in the bulk leads to the Feynmann (retarded) Green function on the boundary by the same procedure.…”
Section: Jhep04(2006)044mentioning
confidence: 99%
“…, N → P (N) as one circles the point of insertion of σ P [58]. For example, if we have σ (12,...,n) (z) at z = 0, we should impose the boundary condition on the fields x A (z), ψ A (z) as follows, 10) where '+' is for the NS sector and '−' is for the R sector. This permutation of CFTs can be conveniently realized by going to a covering space on which the fields of the CFT are single valued [64,66].…”
Section: A2 Orbifold Cftmentioning
confidence: 99%
“…In this way, it is possible to compute and compare quantities such as the entropy of the system and correlation functions of fields/operators [4][5][6][7][8][9][10][11][12]. Recent work [13][14][15][16][17][18][19][20][21] has shown that in some cases one can do even better by extending this relation to the regime where the bulk geometry receives large corrections from higher derivative string and loop effects.…”
Section: Introductionmentioning
confidence: 99%
“…This is necessarily restricted to situations in which the bulk metric fluctuates modestly, whereas we propose a non-perturbative formulation. Yet another general approach is to try to enter the horizon by a variety of analytic continuations of external (Lorentzian or Euclidean) correlators [45,[56][57][58][59]. Our work has this aspect to it, but it is governed and understood from a physical perspective in which analytic continuation merely provides…”
Section: Relation To the Literaturementioning
confidence: 99%